Current Topics in Salmonella and Salmonellosis 2017
DOI: 10.5772/67399
|View full text |Cite
|
Sign up to set email alerts
|

Preharvest Salmonella Risk Contamination and the Control Strategies

Abstract: Salmonella is present in most food production environments and can enter the food supply at any stage of food production from farm to fork. Control strategies for Salmonella include preharvest and postharvest aspects. Preharvest approach is very important because as a result of large-scale production, many animals could be infected with Salmonella serotypes during the primary production, causing human salmonellosis by consuming meat, milk, and eggs or foods containing ingredients of animal origin. The first st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…A number of studies have highlighted the role of flies, rodents, and wild birds in the transmission and perpetuation of Salmonella infection among poultry flocks and other farm animals. Rodents can carry Salmonella in their intestinal tracts asymptomatically (Zamora-Sanabria and Alvarado, 2017), and are the reported vectors and amplifiers of Salmonella in farm animals (Meerburg and Kijlstra, 2007). Rodent droppings can remain a source of Salmonella contamination for up to 3 mo following infection with the feaces of sick animals (Davies and Wray, 1995; Zamora-Sanabria and Alvarado, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have highlighted the role of flies, rodents, and wild birds in the transmission and perpetuation of Salmonella infection among poultry flocks and other farm animals. Rodents can carry Salmonella in their intestinal tracts asymptomatically (Zamora-Sanabria and Alvarado, 2017), and are the reported vectors and amplifiers of Salmonella in farm animals (Meerburg and Kijlstra, 2007). Rodent droppings can remain a source of Salmonella contamination for up to 3 mo following infection with the feaces of sick animals (Davies and Wray, 1995; Zamora-Sanabria and Alvarado, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Rodents can carry Salmonella in their intestinal tracts asymptomatically (Zamora-Sanabria and Alvarado, 2017), and are the reported vectors and amplifiers of Salmonella in farm animals (Meerburg and Kijlstra, 2007). Rodent droppings can remain a source of Salmonella contamination for up to 3 mo following infection with the feaces of sick animals (Davies and Wray, 1995; Zamora-Sanabria and Alvarado, 2017). On the other hand, flies also act as mechanical vectors, aiding transmission of the bacteria from one farm to another.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, the worldwide emergence of several resistant strains of Salmonella emphasizes a major food safety hazard. In poultry, Salmonella is responsible for either clinical diseases or asymptomatic subclinical infections, the latter is referred to as "carriers" [46]. In earlier poultry studies, it has been shown that subclinical infection in chickens can be persistent for >22 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Much progress has been made during the last 40 to 50 years in reducing Salmonella transmission through the food chain to humans. Management practices have had a major impact by preventing wild birds from access to poultry housing facilities, by controlling rodents, and by eliminating components of poultry feeds from fish and animals often contaminated with Salmonella (11,12) At the same time, efforts were being made to develop other means of preventing Salmonella infection of poultry. These included use of competitive exclusion (CE) products by altering the microbiome to favor microbes that would competitively decrease the prevalence of Salmonella (13).…”
mentioning
confidence: 99%